POTENSI WISATA ALAM AIR TERJUN TOMPA IKA DI DESA SAKITA KECAMATAN BUNGKU TENGAH KABUPATEN MOROWALI - Hasmida, Hasmida; Sudhartono, Arief (Jurnal Warta Rimba, 2020)
Tompa waterfall ika is one of the natural attractions in sakita village bungku district middle morowali district central Sulawesi province. Tompa waterfall natural tourism can be developed so that the community can use it for their interests with its conservation and rehabilitation activities. This research was conducted for two months, june to july 2019. This research is located in the Tompa Ika waterfall in Sakita Village, Bungku Sub-District, Central Morowali Didtrict. The purpose of this research is to find out the potential of natural tourism in Tompa Ika waterfall. The method used in this research is descriptive qualitative. Data collection using the method of observation, interviews and documentation. Sampling from this research that is by purposive sampling and the respondents consist of people who are considered to have involvement in the management and utilization of the natural attractions of Tompa Ika waterfalls. The analysis of the area of operation of objects and natural attractions (ADO-ODTWA). This attraction has the potential for uniqueness of attractive natural resources, prominent natural tourism activities and cleanliness of tourist attraction locations. The criteria of attractiveness is 83,3% and includes a feasible category. The criteria of access are limited to 91,66% and are categorized as feasible. For visitor facilities  and infrastructure criteria with a 100% eligibility index and  included in the  feasible  category. Accommodation criteria 33,33% and included in the improper category. From the overall criteria it can be  concluded that the Tompa Ika waterfall natural tourism with a feasibility level of 79,88% is suitable to developed as a tourist spot.Keywords: Kriteria daya tarik, Aksesibilitas, Akomodasi, Sarana dan prasarana